Search and Predictability of Prices in the Housing Market - Møller, Stig Vinther; Pedersen, Thomas; Montes Schütte, Erik Christian; Timmermann, Allan (Management Science, 2024)
We develop a new housing search index (HSI) extracted from online search activity on a limited set of keywords related to the house-buying process. We show that HSI has strong predictive power over subsequent changes in house prices, both in-sample and out-of-sample and after controlling for the effect of commonly used predictors, and relate our findings to models of search-induced frictions. Our results imply that search data can be used as an early indicator of where the market is going. This paper was accepted by David Sraer, finance. Funding: We acknowledge support from the Danish Finance Institute and from the Independent Research Fund Denmark [Grants DFF 7024-00020B and DFF 7015-00017B]. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4672 .